Clinical case of torpid course of metastatic triple negative breast cancer - E. P. Kulikov; E. Yu. Golovkin; S. A. Mertsalov; I. I. Vinogradov; M. V. Borisova; S. Kh. Vagapova (Сибирский онкологический журнал)
Background. Breast cancer is the most common cancer and the leading cause of cancer death in women worldwide. The presence of an unfavorable molecular biological subtype significantly worsens the prognosis, making it necessary to individualize treatment strategy for each patient.The aim of the study was to demonstrate the achievement of long-term remission in the treatment of metastatic triple-negative breast cancer. Case description. A 42-year-old patient presented to Ryazan Oncologic Dispensary in October 2006 with complaints of lump in her left breast. She was diagnosed with stage cT2N0M0 triple-negative carcinoma of the left breast. She underwent radical mastectomy for left breast cancer (October, 2006). Disease progression (metastases to lungs and mediastinal lymph nodes) occurred in June 2009. The patient received 6 courses of polychemotherapy according to the FAC regimen with a favorable response. In February 2011, the patient was found to have metastatic lesion in the brain, which was surgically removed in March, 2011. She received metronome chemotherapy. Recurrence of brain metastasis occurred 6 months after chemotherapy. The patient received external beam radiation therapy, which resulted in tumor regression, and metronomic chemotherapy was continued with a positive effect. The patient was followed up for 6 years with no evidence of disease progression. In July 2019, the follow-up examination revealed stage cT2N0M0 triple-negative cancer in the right breast. The patient underwent radical mastectomy for the right breast and 8 courses of adjuvant polychemotherapy (4 courses of AC + 4 courses of paclitaxel). The patient is alive with no signs of disease progression.Conclusion. This clinical case demonstrated personalized approach to the treatment of patients with triple-negative breast cancer. Fifteen years had passed since the detection of the primary tumor. During this time, the disease progressed three times, and breast cancer was diagnosed on the opposite side. Combined modality treatment including chemotherapy, surgery and radiotherapy allowed satisfactory results to be achieved. The patient is still alive with no signs of disease progression.